2018
DOI: 10.1002/lary.27716
|View full text |Cite
|
Sign up to set email alerts
|

Tra2β silencing suppresses cell proliferation in laryngeal squamous cell carcinoma via inhibiting PI3K/AKT signaling

Abstract: Objectives/Hypothesis Transformer‐2 protein homolog beta (Tra2β) generally plays an important role in various human cancers, but its role and the underlying mechanisms in laryngeal squamous cell carcinoma (LSCC) remained unknown. So this study aimed to assess the clinical significance and regulatory mechanisms of Tra2β in LSCC. Study Design Laboratory analysis. Methods Expression of Tra2β was compared in human LSCC tissue samples and paired adjacent normal tissue samples. The in vitro effects of Tra2β expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…TRA2β is associated with poor differentiation, lymph node metastasis, and advanced clinical stage of laryngeal cancer. It promotes proliferation, growth, invasion, and migration, and inhibits apoptosis by activating PI3K/AKT (21). Our findings also indicated that HTR7 promoted laryngeal cancer proliferation and growth through the PI3K/AKT pathway.…”
Section: Discussionsupporting
confidence: 67%
“…TRA2β is associated with poor differentiation, lymph node metastasis, and advanced clinical stage of laryngeal cancer. It promotes proliferation, growth, invasion, and migration, and inhibits apoptosis by activating PI3K/AKT (21). Our findings also indicated that HTR7 promoted laryngeal cancer proliferation and growth through the PI3K/AKT pathway.…”
Section: Discussionsupporting
confidence: 67%
“…Prior researches have demonstrated that PI3K-Akt pathway effects on the initiation and progression of LSCC [13,[26][27][28]. Based on the previous findings, the present study further analyzed the potential clinical values of COL4A2, LAMC2, and SPP1, which enriched in PI3K-Akt signaling pathway.…”
Section: Diagnosis and Prognosis Values Of Hub-genes Associated With ...mentioning
confidence: 79%
“…For example, proliferation of laryngeal cancer cells is promoted by miR132 through targeting FOXO1 leading to the activation of PI3K/ AKT pathway (Lian et al, 2016). TRA2β increases proliferation, promotes metastasis and inhibits apoptosis of laryngeal cancer cells by activating PI3K/AKT pathway (Ni et al, 2019). Thus, PI3K/Akt pathway has a main role in cellular survival and is therefore also known as the pathway of anti-apoptosis (Simpson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%